Towards a Semantic Framework for Lifelong Integrated Competency Management and Development. (15th August 2019) - Rezgui, Kalthoum; Mhiri, Hédia
Abstract: In the domain of technology-enhanced competency-based learning and training, there is an increased interest in the integration of competency-related information for supporting competency-driven decision-making purposes. Indeed, since competency development draws upon several related areas, including teaching subjects, instructional design, learning resource annotation, e-Portfolios and motivated by the need for an integrated and semantic-based approach to competency management and development, a series of ontological structures have been formalized and developed for each of these areas. This paper aims to provide a framework specification for lifelong competency management and development, called LCMDF. The main advantage of this framework lies in its ability to provide a unifying semantic foundation in the form of a set of controlled vocabularies for describing competencies and their related details within the contexts of technology-enhanced competency-based learning and training. Moreover, this framework provides a novel integrated model to support a wide range of use cases. The proposed framework results from reusing widespread international standards for competency modeling which helps designing and implementing interoperability architecture of semantically-enhanced competency-based learning/human resource (HR) systems.